Hermeneutics in Transition: Three Hermeneutical Horizons of Slavic Evangelicals in the Post-Soviet Period - Alexander NEGROV (Богословські роздуми: Східноєвропейський журнал богословʼя)
This article seeks to identify some of the more common trends within evangelical biblical interpretation produced by current circumstances in the countries of the former Soviet Union. The author argues that the present religious-cultural context, the ongoing political-economic shift, and theological education are affecting the way the Bible is interpreted by these countries’ evangelicals. Today’s evangelical Christians face the challenge of approaching the biblical texts in the midst of constant change related to the historic transformation that their country, society, and churches are undergoing. Within this unsettled context, a reinterpretation of the biblical texts frequently occurs, and the search to discover new meanings within them continues. The author attempts to formulate a framework for the post-communist hermeneutical debate among Slavic evangelicals.